Selective oxidation of o‐chlorotoluene to o‐chlorobenzaldehyde catalyzed by (Co, Mn)(Co, Mn)2O4 catalysts. (25th January 2018) - Liu, Jiangyong; Zhang, Yayun; Yan, Xiaodong; Wang, Zihao; Wu, Faming; Fang, Simeng; Jian, Panming
Abstract: Catalytic oxidation of chlorotoluene is an important reaction for the production of chlorobenzaldehyde. Many works have focused on the oxidation of p ‐chlorotoluene, while little attention has been paid to the oxidation of o ‐chlorotoluene (OCT). Herein, we, for the first time, report on the selective oxidation of OCT to o ‐chlorobenzaldehyde (OCBD) with a cobalt‐manganese composite oxide ((Co, Mn)(Co, Mn)2 O4 ) as a catalyst and O2 as a green and free oxidant. The Co centres are slightly more active than the Mn centres toward the catalytic oxidation of OCT. However, the Co sites seem active enough to further oxidize the OCBD to o ‐chlorobenzoic acid. It is also found that the crystallinity of the (Co, Mn)(Co, Mn)2 O4 catalysts or the valence state of the surface cations in the catalysts affects the activity and selectivity. Abstract : A cobalt‐manganese composite oxide ((Co, Mn)(Co, Mn)2 O4 ) was employed as a catalyst and O2 as a green and free oxidant for the selective oxidation of o ‐chlorotoluene to o ‐chlorobenzaldehyde.